Investigations Into Chemically Stabilized Four-Letter DNA for DNA-Encoded Chemistry - Potowski, Marco; Kunig, Verena B. K.; Eberlein, Lukas; Škopić, Mateja Klika; Vakalopoulos, Alexandros; Kast, Stefan M.; Brunschweiger, Andreas (Frontiers in Chemistry, 2022)
DNA-encoded libraries are a prime technology for target-based small molecule screening. Native DNA used as genetic compound barcode is chemically vulnerable under many reaction conditions. DNA barcodes that are composed of pyrimidine nucleobases, 7-deazaadenine, and 7-deaza-8-azaguanine have been investigated for their suitability for encoded chemistry both experimentally and computationally. These four-letter barcodes were readily ligated by T4 ligation, amplifiable by Taq polymerase, and the resultant amplicons were correctly sequenced. Chemical stability profiling showed a superior chemical stability compared to native DNA, though higher susceptibility to depurination than a three-letter code based on pyrimidine DNA and 7-deazaadenine.